Android-Based Student Assessment Information System For Sds Setia Bakti - Widyastuti, Reni; Widiyastuti, Anggi Arini; Pamungkas, Elang Widya; Susilo, Tri (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
The Indonesian government implements a 9-year compulsory education program for all Indonesian citizens, so its implementation requires the participation of various government & private institutions and institutions. Yayasan Setia Bakti is a non-governmental educational institution that plays an active role in education, especially basic education, namely SDS Setia Bakti, which was founded in 1970. Currently under the leadership of Mr. H.M.Muchaeri as chairman of the foundation wants to improve the student data processing system in order to improve the quality of the school because SDS Setia Bakti is still implementing manual processing and storage and paper media as storage so that it takes longer which can make it difficult to store & make reports to the basic education office and parents of students. This research is a solution to overcome these problems where the student value data processing system is made using a system development model, namely Prototyping and tools in system development with UML and mobile-based programs, namely android. This system is expected to provide better services so that schools get more benefits that increase the trust of parents of students.